Pengaruh Bullying Terhadap Minat Belajar Peserta Didik Kelas X dan XI di SMA Trisoko Jakarta Timur - Iin Asikin; Burhan Burhan; Susalti Nur Arsyad (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of the study was to determine whether there was an effect of bullying on the learning interest of class X and XI students. The research method used is a survey method with a correlational approach. That is a study to determine the effect of the independent variable (bullying) with related variables (student learning interest). The population in this study were students of class X and XI SMA Trisoko Jakarta, totaling 89 people. The sample was determined by 89 people, carried out with a saturated sampling technique. Through calculations obtained rxy of 0.251 which means that there is a low influence between bullying on the learning interest of students in class X and XI at Trisoko High School Jakarta. Analysis of the coefficient of determination obtained 6.3001%. This shows that the contribution of variable X (bullying) to variable Y (student learning interest) is 6,3001%, and the remaining 93,6999% is determined by other factors not examined in the study. this. This effect was tested using statistical hypothesis testing (T test) which obtained tcount > t table or 2,418 > 1,991, indicating that there was a positive and significant influence between the X variable (bullying) on ​​the Y variable (student learning interest) in class X and XI.